Uganda - Demography and Economic Growth in Uganda - World Bank (World Bank, 2012)
Uganda has one of the youngest and most rapidly growing populations in the world. The most important demographic issue for Uganda is related to the age structure rather than the overall size of its population. A very young population represents a major challenge for Uganda in the short and medium term. In order to change its population age structure faster, Uganda needs to accelerate the demographic transition, namely the shift from high levels of mortality and fertility to low levels of mortality and fertility. Once mortality (especially infant and child) and fertility rates begin to fall, young age dependency ratio will follow the same trend albeit with some lag. This will have positive - and quite possibly major - implications for the economic growth. Given the high fertility and reduced mortality over the last several decades, Uganda's population will be growing rapidly over the next several decades. Uganda's economic future looks brighter under assumptions of demographic change.